2004
DOI: 10.1111/j.1365-2249.2004.02522.x
|View full text |Cite
|
Sign up to set email alerts
|

RecombinantMycobacterium bovisbacillus Calmette-Guérin (BCG) expressing mouse IL-18 augments Th1 immunity and macrophage cytotoxicity

Abstract: SUMMARY has been demonstrated to synergize with BCG for induction of a T-helper-type 1 (Th1) immune response. Since successful treatment of superficial bladder cancer with BCG requires proper induction of Th1 immunity, we have developed a recombinant (r) BCG strain that functionally secretes mouse (m) IL-18. This rBCG-mIL-18 strain significantly increased production of the major Th1 cytokine IFN-g in splenocyte cultures, at levels comparable to that elicited by control BCG plus exogenous rIL-18. IFN-g producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 63 publications
4
68
0
3
Order By: Relevance
“…We demonstrate here for the first time that the rBCG strain increased macrophage phagocytic activity and induced higher production of NO, iNOS, and pro-inflammatory cytokines such as TNF-α and IL-1β than those produced by parent BCG-infected macrophages. The results are consistent with our previous finding 39 and other studies [46][47][48][49][50] demonstrating that a recombinant BCG is more potent in activating macrophages than parental BCG. These findings support our previous data showing that the rBCG vaccine capable of inducing a strong cell mediated and humoral immune responses in animal model.…”
Section: Discussionsupporting
confidence: 93%
“…We demonstrate here for the first time that the rBCG strain increased macrophage phagocytic activity and induced higher production of NO, iNOS, and pro-inflammatory cytokines such as TNF-α and IL-1β than those produced by parent BCG-infected macrophages. The results are consistent with our previous finding 39 and other studies [46][47][48][49][50] demonstrating that a recombinant BCG is more potent in activating macrophages than parental BCG. These findings support our previous data showing that the rBCG vaccine capable of inducing a strong cell mediated and humoral immune responses in animal model.…”
Section: Discussionsupporting
confidence: 93%
“…While the vaccine has been engineered to secrete immunostimulatory agents, such as cytokines (20,25,27) and, more recently, chemokines (33), we demonstrate here, for the first time, that the hemopoietic growth factor Flt3L can be expressed and secreted by a bacterial system in a functional form (Fig. 3).…”
Section: Discussionmentioning
confidence: 62%
“…Several recombinant BCG (rBCG) strains secreting immunepotentiating molecules have been developed with the objective of manipulating the immunological milieu in situ [16][17][18][19]. We have shown that subcutaneous delivery of BCG expressing APC growth factors can improve anti-BCG immunity and in some cases lead to improved protective efficacy; however, these vaccines were unable to improve protection against pulmonary growth of M. tuberculosis in the mouse [18,19].…”
Section: Introductionmentioning
confidence: 99%